2010
DOI: 10.1017/s0022381610000174
|View full text |Cite
|
Sign up to set email alerts
|

Party Power or Preferences? Quasi-Experimental Evidence from American State Legislatures

Abstract: Can majority parties control legislative outcomes by controlling the agenda, or are roll call patterns simply the product of legislators' preferences? We argue that, holding members' preferences constant, the majority party's ability to set the agenda gives it the power to influence legislative outcomes. We present the implications of this view of party power formally, and then explore them empirically in two quasi-experiments from American state legislatures. In both, agenda control varies while legislator pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 16 publications
1
55
0
1
Order By: Relevance
“…Thus, the emphasis of the party cartel theory is the negative agenda power afforded to the majority party through chamber rules (Cox and McCubbins ). Subsequent research has examined the extent of negative agenda control possessed by the majority party in the U.S. context (Cox, Kousser, and McCubbins ; Finocchiaro and Rohde ; Gailmard and Jenkins ) as well as outside the United States (Aleman ; Amorim Neto, Cox, and McCubbins ; Cox, Heller, and McCubbins ; Cox, Masuyama, and McCubbins ).…”
Section: Parties As Procedural Cartelsmentioning
confidence: 99%
“…Thus, the emphasis of the party cartel theory is the negative agenda power afforded to the majority party through chamber rules (Cox and McCubbins ). Subsequent research has examined the extent of negative agenda control possessed by the majority party in the U.S. context (Cox, Kousser, and McCubbins ; Finocchiaro and Rohde ; Gailmard and Jenkins ) as well as outside the United States (Aleman ; Amorim Neto, Cox, and McCubbins ; Cox, Heller, and McCubbins ; Cox, Masuyama, and McCubbins ).…”
Section: Parties As Procedural Cartelsmentioning
confidence: 99%
“…Research suggests that rules governing committees and vote scheduling, which vary by chamber and are affected by party control (Cox et al, 2010), shape the legislative process within each chamber (Anzia and Jackman, 2013;Jackman, 2014;cf. Diermeier and Vlaicu, 2011).…”
Section: Theoretical Perspectives On Chamber Differencesmentioning
confidence: 99%
“…It is clear the action of the governor is influenced by his party identification and this was the case for legislators as well (Cox, 2010). Republicans in the legislature had been calling for restrictive immigration laws since 2001 but it was not until 2006 that they found that Democrats were willing to work with them on several of their proposals.…”
Section: Political Leaders On Immigrationmentioning
confidence: 99%